2003
DOI: 10.1034/j.1600-079x.2003.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of indoleamines on in vitro ascorbate‐Fe2+dependent lipid peroxidation of rod outer segment membranes of bovine retina

Abstract: : Rod outer segment membranes (ROS) are highly vulnerable to autooxidation because of their high content of long chain polyunsaturated fatty acids (PUFAs). Melatonin and N‐acetylserotonin are indoleamines synthesized in the pineal gland, retina and other tissues. These compounds are free radical scavengers and indirect antioxidants because of their stimulatory effect on antioxidative enzymes. We compared the in vitro protective effect of melatonin and N‐acetylserotonin on the ascorbate‐Fe2+ induced lipid perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
(31 reference statements)
0
26
0
Order By: Relevance
“…The concentration of each compound required to inhibit 50% of the lipid peroxidation (IC50) was 9.82 mM for melatonin and 0.43 mM for Nacetylserotonin, respectively. Nacetyl serotonin showed a protective effect about 20 times higher than that of melatonin; [94] significance of this apparent difference remains unknown; however, caution is needed when interpreting these results since the role of N-acetyl serotonin as an in vivo antioxidant remains essentially uninvestigated. We have shown that the indoleamines melatonin and N-acetyl serotonin protects rat liver microsomes against lipid peroxidation induced by ascorbate-Fe 2+ in a concentrationdependent manner.…”
Section: Meatonin and N-acetyl Serotonin Inhibit Selectively Enzymatimentioning
confidence: 82%
“…The concentration of each compound required to inhibit 50% of the lipid peroxidation (IC50) was 9.82 mM for melatonin and 0.43 mM for Nacetylserotonin, respectively. Nacetyl serotonin showed a protective effect about 20 times higher than that of melatonin; [94] significance of this apparent difference remains unknown; however, caution is needed when interpreting these results since the role of N-acetyl serotonin as an in vivo antioxidant remains essentially uninvestigated. We have shown that the indoleamines melatonin and N-acetyl serotonin protects rat liver microsomes against lipid peroxidation induced by ascorbate-Fe 2+ in a concentrationdependent manner.…”
Section: Meatonin and N-acetyl Serotonin Inhibit Selectively Enzymatimentioning
confidence: 82%
“…Leaden and Catalá [67] and García et al [68] found that NAS strengthened biological membranes against oxidative stress, which may be related to its ability to reduce lipid peroxidation. Additional studies have shown that NAS also exerts protective effects against peroxidative damage of neurons [6971], lung epithelial cells [72], erythrocytes [73], testicular cells [74], retinal cells [75, 76], and lymphocytes [77]. The data imply that the antioxidant effect of NAS is independent of melatonin and stronger than that of melatonin [76, 78].…”
Section: Discussionmentioning
confidence: 99%
“…This compound is a free radical scavenger and indirect antioxidant because of its stimulatory effect on antioxidative enzymes like MLT. Comparison of the in vitro protective effect of MLT and N-acetylserotonin on the ascorbate-Fe 2+ induced lipid peroxidation of PUFAs located in ROS membranes [58] showed that the protective effect of N-acetylserotonin against ascorbate-Fe 2+ -induced oxidative damage was approximately 20 times higher than that of MLT. MLT and tryptophan derivatives such as N-acetylserotonin possess free radical scavenging activity.…”
Section: Melatonin Related Antioxidant Comp-oundsmentioning
confidence: 98%